Pengembangan Modul IPA Materi Tata Surya Berbasis Perspektif Ayat-Ayat Al Qur’an Pada SMPIT dan MTs - Sugiharto, Bambang; Cintamulya, Imas (Universitas Sebelas Maret, 2018)
This research is a development research with the aim to produce product in the form of IPA Module of Solar Matter Based on Perspective Al-qur'an Verses In SMPIT and MTs class VII. The problems in this study include, the limited module used as a reference of learning that contain the relationship between science materials and verses of the Qur'an. So that raises the formulation of the problem how to develop IPA module Solar Problem Material Based on Perspectives Al-qur'an verses are valid, practical and effective. This research is expected to facilitate the comprehension of students in understanding the science materials related to the verses of Al-Qur'an and not only to increase the knowledge of students but also to play a supporting role in filling the students character education. This research development uses R & D method (Research and Development) with 4-D development model (Four D Model) with three stages of research that is Define (define), Design (design) and Develop (development). The module validation test generated in this study was conducted by 3 expert validators in the field of science education.The trials were conducted on 20 MTs students. Manbail Futuh Jenu class VII. Data collection to test the practicality of this research using observation and test techniques. Collecting data of effectiveness using questionnaire technique. The results show that the modules developed have met the valid, practical and effective criteria.